Implementasi Pembelajaran Jarak Jauh RA Bani Malik Ledug, Kecamatan Kembaran, Kabupaten Banyumas - -, Wulan Anggraeni (Educreative : Jurnal Pendidikan Kreativitas Anak, 2021)
This research uses qualitative methods that seek to understand field phenomena descriptively. The research location taken was at an early childhood education institution, RA Bani Malik Ledug, Twin of Banyumas. RA Bani Malik is still carrying out learning through whatsapp application. The data source collected comes from interview, observation and documentation data. For data verification is done using Miles and Huberman analysis, from data collection to data presentation, and triangulation methods are carried out. The results showed that the implementation of distance learning with the theme of The Universe and My Body is Healthy and Strong, done with the whatsapp application through the video call feature, because it can only use video calls with eight users, RA Bani Malik divides each class into three groups. Before the learning with this theme was carried out, RA Bani Malik first carried out the planning. This planning is carried out every week, to determine the activities that will be carried out in accordance with the theme.